Notch pathway promotes ovarian cancer growth and migration via CXCR4/SDF1α chemokine system. (September 2015) - Chiaramonte, R.; Colombo, M.; Bulfamante, G.; Falleni, M.; Tosi, D.; Garavelli, S.; De Simone, D.; Vigolo, E.; Todoerti, K.; Neri, A.; Platonova, N.
Abstract: Ovarian cancer is the most deadly gynecological malignancy. Understanding the molecular pathogenesis of ovarian cancer is critical to provide new targeted therapeutic strategies. Recent evidence supports a role for Notch in ovarian cancer progression and associates its dysregulation to poor overall survival. Similarly, CXCR4/SDF1α signalling correlates with ovarian cancer progression and metastasis. Recent findings indicate that Notch promotes CXCR4/SDF1α signalling and its effect on cell growth and migration; nonetheless, up to now, the association between Notch and CXCR4/SDFα in ovarian cancer has not been reported. Thereby, the aim of this study was to investigate if Notch and CXCR4/SDF1α cooperate in determining ovarian cancer growth, survival and migration. To address this issue, Notch signalling was inhibited by using γ-secretase inhibitors, or upregulated by forcing of Notch1 expression in ovarian cancer cell lines. Our results indicated that Notch activity influenced tumour cell growth and survival and positively regulated CXCR4 and SDF1α expression. CXCR4/SDF1α signalling mediated the effect of Notch pathway on ovarian cancer cell growth and SDF1α-driven migration. Additionally, for the first time, we demonstrated that Notch signalling activation can be detected in ovarian cancer specimens by immunohistochemistry analysis of the Notch transcriptional target, HES6 and is positively correlated with high expression levels of CXCR4 and SDF1α. Our results demonstrate that Notch affects ovarian cancer cell biology through the modulation of CXCR4/SDF1α signalling and suggest that Notch inhibition may be a rationale therapeutic approach to hamper ovarian cancer progression mediated by the CXCR4/SDF1α axis.